COMPARATIVE ADSORPTION OF Pb²⁺ USING EDTA-MODIFIED BANANA PEEL (Musa acuminata) AND PALM KERNEL SHELL (Elaeis guineensis) - Gurumyen, Kenneth Koomtoe (FUDMA Journal of Sciences, 2026)
Heavy metal contamination of water resources, particularly by lead, poses serious environmental and public health risks due to its toxicity and bioaccumulation potential. In many developing regions, conventional water treatment technologies are costly and energy-intensive, necessitating affordable and sustainable alternatives. This study investigated the adsorption performance of two abundant agro-wastes in Nigeria (banana peel and palm kernel shell) as bioadsorbents for Pb²⁺ removal from aqueous solutions. The objective was to evaluate the effectiveness of raw and ethylenediaminetetraacetic acid (EDTA)-modified biomaterials and to assess the influence of surface modification on adsorption efficiency. Batch adsorption experiments were conducted using 5.0 g of adsorbent in 100 mL of 0.01 M Pb(CH₃COO)₂ solution with a contact time of 4 h under ambient conditions. Residual Pb²⁺ concentrations were determined using gravimetric precipitation as PbCO₃ and Atomic Absorption Spectroscopy (AAS). Gravimetric results showed that EDTA-modified banana peel achieved the highest Pb²⁺ removal efficiency (≈99.3%), reducing the equilibrium concentration from 1736.94 mg L⁻¹ (control) to 15.51 mg L⁻¹, followed by modified palm kernel shell with ≈97.8% removal and a residual concentration of 46.53 mg L⁻¹. Unmodified banana peel and palm kernel shell showed lower efficiencies, with equilibrium Pb²⁺ concentrations of 170.59 and 356.69 mg L⁻¹, respectively. Although high removal efficiencies were obtained, residual Pb²⁺ concentrations remained above the World Health Organization guideline value of 0.01 mg L⁻¹, indicating the need for further optimization. The study demonstrates that EDTA-modified agro-wastes are effective, low-cost bioadsorbents for Pb²⁺ remediation in aqueous systems.
Keywords: Pb²⁺ adsorption; Agro-waste adsorbents; Musa acuminata; Elaeis guineensis; Surface modification; Aqueous remediation